TASTE ABATEMENT AND CHARACTERIZATION OF DISPERSIBLE TABLETS OF ARTEMETHER PREPARED BY HOT MELT EXTRUSION - Sonar, Yogesh A.; Bele, Mrudula H.; Sonar, Nitin H.; Bagul, Vishal S.; Shimpi, Prashik S. (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of this study was to formulate and evaluate a taste-masked formulation using hot melt extrusion approach for artemether. Methods: Taste masking of artemether was done by preparing solid dispersion with coating polymer kollicoatsmartseal 30D using hot melt extrusion. The prepared solid dispersion was subjected to taste masking evaluation like sensory evaluation parameters against five levels set for taste evaluation using artemether as control standard along with in vitro release studies in simulated salivery fluid. After taste evaluation of solid dispersion was subjected to the formulation of dispersible tablets by direct compression method. The final taste masking evaluation of dispersible tablets of solid dispersion containing artemether were done by a sensory evaluation panel of nine members along with in vitro release study in simulated salivary and gastric fluid. Results: The percent drug content was found 35.09±0.06 % in solid dispersion. The drug excipients compatibility studies performed with the help of FTIR instrument and DSC that indicates there were no interactions between drug and polymers. Solid dispersions (1:1, 1:2, 1:3 drug polymer ratio) of artemether were evaluated by sensory evaluation panel from which 1:3 drug: polymer solid dispersion was found more palatable. Release rate study in simulated salivary fluid shown no release but shows release of drug in simulated gastric fluids which indicates that the drug was taste masked. The optimized batch of dispersible tablets (F1) were subjected for evaluation parameters like dispersion time (70±1.90), wetting time (63±1.86), etc. Dissolution studies of optimized formulation indicated that the polymer does not allow drug to release in simulated salivery pH 6.8 but shows immediate release in simulated gastric pH which also confirms taste masking efficiency of polymer. Final optimized F1 batch evaluated for taste masking evaluation by sensory evaluation panel using pure drug as control standard found to be palatable. Conclusion: It may be concluded that kollicoatsmartseal 30D could mask the taste of the drug in salivary pH and shows drug release at gastric pH which confirms its efficiency for taste masking.